Shedding light on alternative shrimp fishing - Bouwmeester, René (2018)
In search of a less destructive alternative to current shrimp fishing methods, both in terms of bycatch reduction and increasing shrimp-catch in pots, this study aims to analyse the catches and bycatches of different pot designs and alternative attractants for pot fishing on Northern shrimps (Pandalus bore-alis). There are three main objectives: (1. describe how the different pot de-signs and attractants affects shrimp catch and bycatch in abundance and composition, (2. describe how the different pot designs and attractants af-fects the shrimp size distribution of the catch, (3. Describe how the different pot designs and attractants affect the behaviour of shrimps and bycatch in-side the pot by means of underwater video recordings. These objectives were met by conducting an experimental fishing study in Gullmarsfjord, Sweden. As alternative attractant lights in the colours green, white and ultra violet (UV) were tested together with four different pot design. The pots with the larger oval entrances caught significantly more shrimp in CPUE in comparison to the pots with the plastic funnel entrances. In terms of bycatch no significant difference was found between pot designs. The use of lights as an alternative to herring as attractant resulted into a 3.1 times higher shrimp CPUE. However the attractants also effected the bycatch. Especially green light resulted in many gadoids in the bycatch, white light resulted in fewer gadoids than green light, but UV light was found to be the most selec-tive light with the best shrimp catch/bycatch ratio. The results from this study contributes to the development of fishing shrimps with pots by pre-senting how the tested methods increased shrimp catches and affected by-catches.